Answer:
3
Step-by-step explanation:
Answer:
c) -x^3 + x^2 - 1
Step-by-step explanation:
Given: u (x) = x^5 - x^4 +x^2 and v(x) = -x^2
(u/v)(x) = u(x)/v(x)
Now plug in the given functions in the above formula, we get
= (x^5 - x^4 + x^2) / -x^2
We can factorize the numerator.
In x^5 - x^4 + x^2. the common factor is x^2, so we can take it out and write the remaining terms in the parenthesis.
= x^2 (x^3 - x^2 + 1) / - x^2
Now we gave x^2 both in the numerator and in the denominator, we can cancel it out.
(u/v)(x) = (x^3 - x^2 + 1) / -1
When we dividing the numerator by -1, we get
(u/v)(x) = -x^3 + x^2 - 1
Answer: c) -x^3 + x^2 - 1
Hope you will understand the concept.
Thank you.
Sqrt(49)*sqrt (-1) -4 = 7i-4
25.2 / 7.8 = ~ 3.23 hope that helps
Ninety five plus negative two